FAKTOR-FAKTOR PROGNOSTIK MORTALITAS PADA NEONATUS DENGAN ATRESIA ESOFAGUS DI RSUP DR. SARDJITO, YOGYAKARTA, PERIODE JANUARI 2007 â DESEMBER 2012 - , Leecarlo Millano LG ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Esophageal atresia with or without fistula is a congenital defect that causes high morbidity and mortality rate in newborns. Many risk factors causing mortality need to be identified to establish the best approach and decrease the morbidity and mortality. Objective: To identify factors associated with mortality in newborn with esophageal atresia. Method: This retrospective study identified risk factors of mortality in all newborns with esophageal atresia using data from the medical records in Sardjito General Hospital from January 2007 to December 2012. The different factors then analyzed using chi square with level of significance p<0.05. Correlation between length of hospitalization and mortality in neonates wih esophageal atresia postoperative, were analyzed using independent-t test. Result: Anemia and thrombocytopenia (post surgical), and sepsis were identified to have a significant difference in the outcome of mortality (p<0.05). Thrombocytopenia contributed significantly in mortality with OR of 10.857 (95% CI 1.029-114.578) while anemia had a protective effect in mortality with OR of 0.688 (95% CI 0.494- 0.957). Sepsis was a common cause of death in our patients with an OR of 13.333 (95% CI 1.242-143.151). There were no statistically significant between length of hospitalization and mortality in neonates with esophageal atresia postoperative (p=0,110). From all 31 newborns that met our criteria, only 5 survived, and all 5 had one stage surgery. Conclusion: Thrombocytopenia and sepsis were strong factors associated with mortality in newborns with esophageal atresia in our institution. Further studies need to be done with larger sample size to better the precision of the results. Keywords: Esophageal atresia, Prognostic of Mortality, Thrombocytopenia, Sepsis, Anemia